Interactions of Inflammation and E. coli in Crohn's disease - Oberc, Alexander (My University, 2019)
Crohn’s disease (CD) is an inflammatory bowel disease characterised by chronic inflammation with a complex pathophysiology involving host, environmental, and microbial factors. The intestinal microbiota is an important regulator of inflammation within the intestine, and a disruption of the interplay between gut bacteria and host immunity is a key factor in CD development. Intestinal inflammation itself is known to cause changes to the intestinal physiology that affect the ability of various bacteria to survive. Additionally, certain environmental risk factors for CD such as antibiotics are also known for their ability to impact the intestinal microbiota. CD is associated with various changes in the intestinal microbiome including increased colonisation with a group of bacteria known as adherent-invasive Escherichia coli (AIEC). The purpose of this study is to investigate how AIEC interact with antibiotics and intestinal inflammation in vivo. Multiple classes of antibiotics were found to increase the colonisation of AIEC and to increase its persistence. These antibiotics caused a loss diversity in the intestinal microbiome, but this did not explain the increased infectivity of AIEC. Antibiotic-induced inflammation was found to produce metabolites that benefitted AIEC growth in the intestine and similar results were found with chemically-induced inflammation. These results show that AIEC can benefit from both antibiotics and other sources of inflammation through inflammation-derived metabolites, which contributes to a greater understanding of the interactions between AIEC and CD.
Antibiotics and intestinal inflammation increase host susceptibility towards Crohn’s disease-associated adherent-invasive Escherichia coli
Keywords: Crohn's disease; E. coli; Inflammation; Antibiotics